2020
DOI: 10.1007/978-3-030-47426-3_16
|View full text |Cite
|
Sign up to set email alerts
|

HIN: Hierarchical Inference Network for Document-Level Relation Extraction

Abstract: Document-level RE requires reading, inferring and aggregating over multiple sentences. From our point of view, it is necessary for document-level RE to take advantage of multi-granularity inference information: entity level, sentence level and document level. Thus, how to obtain and aggregate the inference information with different granularity is challenging for document-level RE, which has not been considered by previous work. In this paper, we propose a Hierarchical Inference Network (HIN) to make full use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(58 citation statements)
references
References 12 publications
0
46
0
Order By: Relevance
“…We attribute it to the document graph on the entity level, which can better model the semantic information in a document. (3) From the results of ; Tang et al (2020), the BERT-based models showed stronger prediction power for document-level RE. They outperformed the other comparative models on both CDR and DocRED.…”
Section: Resultsmentioning
confidence: 94%
“…We attribute it to the document graph on the entity level, which can better model the semantic information in a document. (3) From the results of ; Tang et al (2020), the BERT-based models showed stronger prediction power for document-level RE. They outperformed the other comparative models on both CDR and DocRED.…”
Section: Resultsmentioning
confidence: 94%
“…For many NLP tasks, contextual information from surrounding sentences can improve the quality of a generated sentence. We have seen this for coreference resolution (Joshi et al, 2019), relation extraction (Tang et al, 2020), and machine translation (Werlen et al, 2018;Macé and Servan, 2019). In this work, we show the effectiveness of including document-level context when rewriting recipes to fit a dietary constraint.…”
Section: Document-level Controlled Generationmentioning
confidence: 86%
“…HIN-GloVe/HIN-BERT base , proposed by Tang et al (2020). Hierarchical Inference Network (HIN) aggregate information from entity-level, sentence-level, and document-level to predict target relations, and use GloVe (Pennington et al, 2014) or BERT base for word embedding.…”
Section: Baselines and Evaluation Metricsmentioning
confidence: 99%